On a reinterpretation of the Higgs field in supersymmetry and a proposal for new quarks - D.E. López-Fogliani; C. Muñoz (Physics Letters B, 2017)
In the framework of supersymmetry, when R-parity is violated the Higgs doublet superfield Hd can be interpreted as another doublet of leptons, since all of them have the same quantum numbers. Thus Higgs scalars are sleptons and Higgsinos are leptons. We argue that this interpretation can be extended to the second Higgs doublet superfield Hu, when right-handed neutrinos are assumed to exist. As a consequence, we advocate that this is the minimal construction where the two Higgs doublets can be interpreted in a natural way as a fourth family of lepton superfields, and that this is more satisfactory than the usual situation in supersymmetry where the Higgses are ‘disconnected’ from the rest of the matter and do not have a three-fold replication. On the other hand, in analogy with the first three families where for each lepton representation there is a quark counterpart, we propose a possible extension of this minimal model including a vector-like quark doublet representation as part of the fourth family. We also discuss the phenomenology of the associated new quarks. Keywords: Supersymmetry, Higgses, Right-handed neutrinos, Phenomenology, New quarks